2022
DOI: 10.1101/2022.11.28.22282784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Closed-loop neurostimulation for epilepsy leads to improved outcomes when stimulation episodes are delivered during periods with less epileptiform activity

Abstract: In patients with drug-resistant epilepsy, electrical stimulation of the brain in response to epileptiform activity can make seizures less frequent and debilitating. When effective, this therapy, known as closed-loop responsive neurostimulation (RNS), produces long-lasting changes in brain dynamics that correlate with clinical outcomes. Since periods with frequent epileptiform activity are less conducive to neuroplasticity, we hypothesize that stimulation timing, specifically stimulation during brain states wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Indeed, a recent study found that the effects of changing RNS stimulation parameters (e.g., frequency, burst duration, and charge density) depend on the initial seizure risk state 47 , with parameter changes effective at reducing seizures in one seizure risk state being less effective during another risk state. Consistent with this, a recent study examining how stimuli were distributed across these low-and high-risk states found improved outcomes when stimulations were delivered preferentially in lowrisk states, i.e., those states less disrupted by ongoing epileptiform activity 48 . RNS stimulation parameters are typically adjusted every few months, remaining constant in the interim.…”
Section: Box 1 | Glossarymentioning
confidence: 53%
See 1 more Smart Citation
“…Indeed, a recent study found that the effects of changing RNS stimulation parameters (e.g., frequency, burst duration, and charge density) depend on the initial seizure risk state 47 , with parameter changes effective at reducing seizures in one seizure risk state being less effective during another risk state. Consistent with this, a recent study examining how stimuli were distributed across these low-and high-risk states found improved outcomes when stimulations were delivered preferentially in lowrisk states, i.e., those states less disrupted by ongoing epileptiform activity 48 . RNS stimulation parameters are typically adjusted every few months, remaining constant in the interim.…”
Section: Box 1 | Glossarymentioning
confidence: 53%
“…Patients with the best outcomes from RNS are those with the greatest ability to reorganize functional network connectivity. Stimuli inducing this plasticity may be more effective when delivered during periods with less epileptiform activity 48 , when endogenous neuroplasticity mechanisms are more active 52,53 .…”
Section: Box 1 | Glossarymentioning
confidence: 99%
“…In our retrospective cohort of 20 patients, we replicated analyses from previous studies [3], [5], [15] to compare the multidien dIEA cycle characteristics in our subjects with existing literature.…”
Section: Multidien Cycles In Interictal Epileptiform Activitymentioning
confidence: 76%
“…Extracting multidien cycles from dIEA counts. We followed a similar methodology as outlined in Baud et al to extract multidien cycles from dIEA activity (Figure 1A) [5], [15]. In brief, for each patient we applied a wavelet transform to the dIEA signal and identified the dominant modes in the average frequency spectrum (peaks in the periodogram) in the range of 3-60 days.…”
Section: Patient Populationmentioning
confidence: 99%
“…For epilepsy, failure to deliver stimulation during seizure events may lead to worse therapeutic outcomes than falsely providing stimulation during non-seizure periods. In fact, there is increasing evidence that the therapeutic benefits of responsive neurostimulation are provided when stimulation is applied during non-seizure states, rather than seizure states [ 16 ]. Similar considerations should be taken when considering other neurological disorders where the therapeutic trade-off may differ in a disease-specific manner, potentially leading to worsened outcomes for patients’ daily activities.…”
Section: Discussionmentioning
confidence: 99%